2019
DOI: 10.1111/odi.13117
|View full text |Cite
|
Sign up to set email alerts
|

Saliva NMR metabolomics: Analytical issues in pediatric oral health research

Abstract: Objectives Saliva metabolome is a promising diagnostic tool concerning oral and systemic diseases. We aimed at establishing a suitable protocol for saliva collection and gauging the relative impacts of gender, dentition stage, and caries on the saliva metabolome of a small children cohort. Subjects and methods A nuclear magnetic resonance‐based metabolomics cross‐sectional study of children saliva (n = 38) compared the effects of: (a) stimulation and unstimulation conditions, and (b) collection through passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 42 publications
2
41
1
Order By: Relevance
“…Lactate and 1-methylhistine are two of the metabolites that emerged in the literature previously in the context of caries activity 31,32 . However, data are conflicting, as increased lactate concentrations in saliva of caries-active children have been reported 32 but not confirmed 33 . In vitro experiments revealed that lactate exposition leads to tooth enamel demineralisation to a greater extent than acetate or propionate 34 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Lactate and 1-methylhistine are two of the metabolites that emerged in the literature previously in the context of caries activity 31,32 . However, data are conflicting, as increased lactate concentrations in saliva of caries-active children have been reported 32 but not confirmed 33 . In vitro experiments revealed that lactate exposition leads to tooth enamel demineralisation to a greater extent than acetate or propionate 34 .…”
Section: Discussionmentioning
confidence: 96%
“…L-serine, L-pyroglutamate and L-threonine showed lower concentrations in the inactive group than in the other two groups, whereas it was opposite for the other two compounds. For nine other amino acids (alanine, aspartate, glutamine, glycine, isoleucine, leucine, proline, taurine, and tyrosine), an increased concentration in swap-collected unstimulated saliva of caries-active children has been shown 33 . However, our data did not confirm this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies have reported conflicting results. For example, butyrate has been found to be increase or decrease in concentration in association with the presence of dental caries [45,46]. It is likely that single metabolites in isolation may not yield sufficient diagnostic specificity for most disease, however multivariate analyses may offer improved accuracy.…”
Section: Current Knowledge Of the Salivary Metabolomementioning
confidence: 99%
“…1 H-NMR analyses have found salivary metabolite profile is independent of sex and BMI when considering net metabolite profile [86], although sex-based metabolic differences have been found when quantifying individual metabolites [91]. Collection method is another caveat for the metabolomic study of saliva, with the use of collection systems as opposed to passive drooling being identified as a potential source of exogenous analytes in samples [46].…”
Section: Current Knowledge Of the Salivary Metabolomementioning
confidence: 99%